2020
DOI: 10.1002/cam4.3584
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and adipose tissue changes in the first phase of treatment of pediatric solid tumors

Abstract: Body composition is increasingly recognized as an important factor in cancer outcomes. Use of computed tomography (CT) in cancer care provides the opportunity to accurately quantify whole‐body lean and adipose tissues from images at the third lumbar spine. We sought to substantiate the use of routinely captured, single‐slice chest CT images at the thoracic level for evaluation of skeletal muscle, residual lean tissue, and adiposity among pediatric solid tumor patients. We performed a retrospective analysis amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 36 publications
1
22
2
Order By: Relevance
“…In accordance with the findings regarding muscle quality, the previously mentioned study in pediatric patients with a solid tumor using CT to assess body composition found no changes in IMAT and skeletal muscle density. 12 In contrast, that study found a decrease…”
Section: Discussionmentioning
confidence: 72%
“…In accordance with the findings regarding muscle quality, the previously mentioned study in pediatric patients with a solid tumor using CT to assess body composition found no changes in IMAT and skeletal muscle density. 12 In contrast, that study found a decrease…”
Section: Discussionmentioning
confidence: 72%
“…The repeated results of search were ruled out. After screening of abstracts, 137 results were chosen for full-text analysis, of which 18 ( 25 , 33 49 ) met the inclusion criteria and were included in the study. A flowchart of study inclusion is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 studies included in this review, 8 ( 25 , 33 37 , 42 , 45 ) examined the prevalence of SO and 8 ( 33 35 , 37 , 43 , 44 , 47 , 48 ) evaluated outcomes related to SO. Seven studies were performed in Europe ( 25 , 34 – 36 , 42 , 45 , 48 ), 5 in the United States ( 38 , 40 , 46 , 47 , 49 ), 3 in Asia ( 33 , 37 , 41 ), and 3 in South America ( 39 , 43 , 44 ). The number of participants ranged from 12 ( 46 ) to 15,392 ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations